Ambivalent Hybridity and Abject Intersubjectivity in Gordimer’s Beethoven was One-Sixteenth Black - et. al., Al-Fartoosi Rana Ali Mhoodar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper attempts to study hybridity in Gordimer’s Beethoven was One-Sixteenth Black. It will concentrate on hybridity as a means of empowering the colonized people’s identity. Hybridity refers to the new-shaped identity in the colonized people’s lands. This identity comprises both the original national identity and the new acquired socio-cultural traditions after colonialism. Therefore, the study will look at hybridity and its negative influences the colonized people’s identity. It will reveal hybridity as an empowerment of the colonized people’s identity due to two reasons. First, the colonized people encounter new cultural traditions that are different form their national traditions. These traditions elevate their national identity. Second, the colonized people interact with new ethnicities that might bring about modern life style to the colonized lands. Hybridity will be approached in this light of ambivalence and identity. Furthermore, the study will demonstrate women’s oppression at the hand of the colonizers and patriarchy through Faludi’s concept of subaltern; and their resistance this oppression. It will study tackles women’s rejection of oppression by applying the concept of abjection. Thus, the study will argue that women gain intersubjectivity the colonizers and the patriarchal system.